Hubungan Pengetahuan Ibu Hamil tentang Tanda Bahaya Kehamilan dengan Kepatuhan Melakukan Antenatal Care (ANC) - Lidia Fitri; Rohmi Rohmi; Cakrawati R (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Pregnancy compliance with antenatal care (ANC) is crucial for preventing pregnancy complications and ensuring the health of both mother and fetus. Knowledge of pregnancy danger signs is a key factor influencing ANC compliance. This study aims to determine the relationship between knowledge of pregnancy danger signs and ANC compliance. The study used a cross-sectional study design, with a sample of 100 pregnant women visiting the Integrated Health Post (Posyandu) and Community Health Center (Puskesmas) in District X, selected using purposive sampling. Data were collected through a structured questionnaire regarding knowledge of pregnancy danger signs and ANC visit records. Data analysis was performed using the Chi-square test to determine the relationship between variables. The results showed that pregnant women with good knowledge had higher ANC compliance than those with poor knowledge (p = 0.001; OR = 3.5). Conclusion: There is a significant relationship between knowledge of pregnancy danger signs and ANC compliance. Antenatal education and counseling efforts are essential to improve maternal compliance.